Reactive Oxygen Species Responsive Cleavable Hierarchical Metallic Supra‐Nanostructure. Issue 38 (13th August 2022) - Choi, Hyunjun; Choi, Bongseo; Han, Jun‐Hyeok; Shin, Ha Eun; Park, Wooram; Kim, Dong‐Hyun
Abstract: A reactive oxygen species (ROS) responsive cleavable hierarchical metallic supra‐nanostructure (HMSN) is reported. HMSN structured with thin branches composed of primary gold (Au) nanocrystals and silver (Ag) nano‐linkers is synthesized by a one‐pot aqueous synthesis with a selected ratio of Au/Ag/cholate. ROS responsive degradability of HMSN is tested in the presence of endogenous and exogeneous ROS. Significant ROS‐responsive structural deformation of HMSN is observed in the ROS exposure with hydrogen peroxide (H2 O2 ) solution. The ROS responsiveness of HMSN is significantly comparable with negligible structural changes of conventional spherical gold nanoparticles. The demonstrated ROS responsive degradation of HMSN is further confirmed in various in vitro ROS conditions of each cellular endogenous ROS and exogeneous ROS generated by photodynamic therapy (PDT) or X‐ray radiation. Then, in vivo ROS responsive degradability of HMSN is further evaluated with intratumoral injection of HMSN and exogeneous ROS generation via PDT in a mouse tumor model. Additional in vivo biodistribution and toxicity of intravenously administrated HMSN at 30‐day post‐injection are investigated for potential in vivo applications. The observed ROS responsive degradability of HMSN will provide a promising option for a type of ROS responsive‐multifunctional nanocarriers in cancer treatment and various biomedical applications. Abstract : A hierarchical metallic supra‐nanostructure (HMSN) composed by primary Au nanobranches connected with Ag nano‐linkers is cleavable in the response to a biological endogenous reactive oxygen species (ROS) and exogeneous ROS condition. Given the challenges of non‐biodegradability and non‐stimuli responsiveness of various potent inorganic nanoparticles, the introduction of ROS‐responsive cleavable HMSN suggests an exciting opportunity for the ROS‐responsive nanocarrier applications.